(GARY) Game-Library: Digital Library Game Based on Augmented Reality to Realize The Golden Indonesian Generation in 2045 - Aini, Nurul; Herdina, Griselda Gian Heris; Nasrullah, Naufal Siddiqi (Proceeding International Conference on Education, 2023)
The problem in lack of reading literacy in Indonesia has become a crucial challenge. In the era of 5.0, this problem must be solved to realize the better future of Indonesian Golden Age in 2045. Therefore, the purpose of this article was to address the problem in reading literacy by utilizing Augmented Reality (AR) in creating Digital Library (DL), and how GARY as a new concept can be used. The present article used conceptual research design particularly in conceptual models and specifically using conceptual description.  This article signified for academics to support the literature review as references for their empirical researches. The findings showed that GARY became a new concept of AR-based library game application to increase students' interest in reading literacy. Moreover, the present article provided a gateway to the empirical study of DL by integrating AR. Future research could examine on the impact of DL by integrating AR.